تصـمـيم ومــحـاكاة سلسلة التجـهـيز الالكترونية دراسـة حـالة في الـشـركة الـعـامـة للـصـناعـات الـصـوفية – مـعـمل 1 أيـار - النجار, صباح مجيد; علي, ازهار زين العابدين (Journal of Economics and Administrative Sciences, 2007)
Supply Chain Management (SCM) attempts to a create a synchronization of the firm’s processes and those of the supplier to match the flow of materials, services, and information with the customer demand. Due to its importance, the SCM has become inevitable to modern companies. Therefore this research work has been conducted to set a theoretical and applied basis to assist the 1 AYAR factory in adopting the Electronic Supply Chain (e-SC).  To accomplish that the searchers applied many tools such as: quantitative and qualitative analysis, process analysis, Visual Basic software, Monte Carlo Simulation to simulation the designed supply chain to compare its performance against the actual performance of the current supply chain at the factory.  The analysis conducted in this research revealed the performance criteria obtained from the simulation runs were better than the actual criteria. Based on the results of this research, the searchers suggest that the factory should think about adopting an e-SC to improve its competitive priorities.